Green synthesis and toxicological evaluation of zinc oxide nanoparticles utilizing Punica granatum fruit Peel extract: an eco-friendly approach - Ali Mohammadi; Negin Hashemi; Mohaddeseh Ghassabzadeh; Ali Sharafi; Alireza Yazdinezhad; Hossein Danafar (Scientific Reports)
Abstract The green synthesis approach for nanoparticle production offers several advantages over traditional physical and chemical methods. Notably, it avoids the use of hazardous chemicals and acts as a cost-effective and eco-friendly process. This study focuses on the green synthesis of zinc oxide nanoparticles (ZnO- NPs) using the Punica granatum fruit peel extract. Punica granatum fruit peel extract was chosen for the environmentally friendly synthesis of ZnO nanoparticles due to its rich composition of bioactive compounds, including polyphenols, flavonoids, and tannins, which function as natural reducing and stabilizing agents. The morphological, structural, and optical observations were confirmed through various techniques such as X- ray diffraction (XRD), UV-Vis spectroscopy, field emission scanning electron microscopy (FE- SEM), Fourier- transform infrared spectroscopy (FT- IR), EDAX and dynamic light scattering (DLS). To further investigate the impact of synthesized nanoparticles, hemolysis and MTT (3-[4, 5- dimethylthiazol- 2- yl]− 2, 5-diphenyl tetrazolium bromide) assays were conducted. The morphology of the resulting nanoparticles was found to be spherical and homogeneous. DLS results show the hydrodynamic size of nanoparticles with a Z-average of 187 nm with polydispersity index (PdI) of nanoparticles to be 0.298 and zeta potential of nanoparticles is -17.6 mV. The results showed that green synthesis using Punica granatum fruit peel extract resulted in significantly higher cell viability in culture compared to traditional chemical synthesis. This finding highlights the project’s aim to emphasize the advantages of the green synthesis approach on HFF-2 cell lines. These results offer powerful evidence for the potential capability of green synthesis ZnO nanoparticles with Punica granatum fruit peel extract opens up a new avenue of research in this area.